Pengembangan Agribisnis African Night Crawler (Eudrilus eugeniae): Peluang, Tantangan, dan Strategi - Nina Lisanty; Rasyadan Taufiq Probojati; Taufan Achmad Gozali Yusuf; Kharisma Satria Pamungkas (Jurnal Penelitian Pendidikan IPA, 2025)
This study, conducted at CV Rumah Alam Jaya in Malang, East Java, Indonesia, aims to explore the potential and challenges of African Night Crawler (ANC) earthworm agribusiness and to formulate sustainable development strategies. Using a mixed-methods case study approach, data were collected through focus group discussions (FGDs), semi-structured interviews, and structured questionnaires (quantitative Likert-scale). Ten FGD participants included worm farmers, extension agents, agribusiness practitioners, and local government officials selected based on their direct involvement in worm agribusiness activities. SWOT factors were identified through thematic analysis of qualitative data, while weights and ratings were derived from FGDs and expert interviews. The analysis places ANC agribusiness in the Growth/Expansion quadrant, supported by easy-to-apply cultivation techniques, strong market potential, and availability of low-cost organic feed. However, it faces internal weaknesses (such as pest vulnerability, limited consumer awareness) and external threats (such as market competition, regulatory constraints). Based on these findings, four integrated strategies are proposed: (1) implementing IoT-based moisture and temperature monitoring, (2) adopting multi-tier rack systems to optimize space use, (3) expanding market access via digital platforms such as Shopee and Tokopedia, and (4) strengthening institutional collaboration and farmer training to improve business sustainability and resilience.